Study of Social Factors Affecting Academic Achievement of Students at Higher Secondary Level - Zehra, Samreen; Naureen, Shazia; Qomi, Hazira (Pakistan Languages and Humanities Review, 2025)
This study explores how social factors affect the academic achievement of higher secondary students, focusing on parental attitudes, teacher support, and peer involvement. Main research objective was to determine the relationship between peer, parents and teachers’ involvement and students’ academic performance. Using a quantitative survey design, data were collected from 320 randomly selected students from three branches of Punjab College, Islamabad. Analysis through descriptive statistics and Pearson’s correlation revealed significant positive relationships between parental encouragement, teacher guidance, and peer collaboration with academic success. Findings indicate that achievement is shaped not only by individual effort but also by students’ social environments. Constructive home–school partnerships, supportive teacher–student interactions, and cooperative peer relationships help in learning motivation and self-efficacy. Study provides empirical evidence from Pakistan’s secondary education context, emphasizing that academic success should be understood as a socially influenced and collaboratively constructed phenomenon. It recommends promoting parent–teacher collaboration and integrating peer-support strategies into school improvement programs.